Voluntary sterilisation of young childless women: not so fast - Buturovic, Zeljka (Journal of medical ethics, 2022)
An increasing number of bioethicists are raising concerns that young childless women requesting sterilisation as means of birth control are facing unfair obstacles. It is argued that these obstacles are inconsistent, paternalistic, that they reflect pronatalist bias and that men seem to face fewer obstacles. It is commonly recommended that physicians should change their approach to this type of patient. In contrast, I argue that physicians’ reluctance to eagerly follow an unusual request is understandable and that whatever obstacles result from this reluctance serve as a useful filter for women who are not seriously committed to their expressed requests for sterilisation. As women already disproportionally bear the birth control burden, less resistance that men might be getting in terms of voluntary sterilisation works to women’s advantage, providing a much needed balance. Societal attitudes towards women and motherhood should not be confused with individual physicians’ reasonable reluctance to jump at a serious elective procedure at fairly mild expression of interest.